Crystal structures of the two salts 2-methyl-1H-imidazol-3-ium nitrate–2-methyl-1H-imidazole (1/1) and 2-methyl-1H-imidazol-3-ium nitrate - Diop, Mouhamadou Birame (Acta Crystallogr E Crystallogr Commun, 2016)
The title salts, C(4)H(7)N(2) (+)·NO(3) (−)·C(4)H(6)N(2), (I), and C(4)H(7)N(2) (+)·NO(3) (−), (II), were obtained from solutions containing 2-methylimidazole and nitric acid in different concentrations. In the crystal structure of salt (I), one of the –NH H atoms of the imidazole ring shows half-occupancy, hence only every second molecule is in its cationic form. The nitrate anion in this structure lies on a twofold rotation axis. The neutral 2-methylimidazole molecule and the 2-methyl-1H-imidazol-3-ium cation interact through N—H⋯N hydrogen bonds to form [(C(4)H(6)N(2))⋯(C(4)H(7)N(2))(+)] pairs. These pairs are linked with two nitrate anions on both sides through bifurcated N—H⋯(O,O) hydrogen bonds into chains running parallel to [001]. In the crystal structure of salt (II), the C(4)H(7)N(2) (+) cation and the NO(3) (−) anion are both located on a mirror plane, leading to a statistical disorder of the methyl H atoms. The cations and anions again interact through bifurcated N—H⋯(O,O) hydrogen bonds, giving rise to the formation of chains consisting of alternating anions and cations parallel to [100].